Analysis of morale and social-kinetic cohesion in young football players - Hassan , Muhsin M.; Fadel , Bashar Ab.; Abd Al Zahra , Mahmood Ab.; Luabi, Sura I. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of the present study was to identify the morale and social-kinetic cohesion of young football players and also to identify the relationship between morale and social-kinetic cohesion in football. The players of the Kufa Sports Club constituted the research community for the study. A total of 25 players of the club were present in the research community for the sports season (2020-2021). In the present study, many tools, devices, and aids were used for the purpose of data collection. The equipment and tools used for assessment, observation and for data collection included the morale scale and the social-kinetic cohesion scale. Based on the present findings, the researchers concluded that the players of the Kufa Club of the youth football category possess high morale and good social cohesion. There is a positive relationship between the morale and the social-kinetic cohesion of the Kufa Youth Football Club players.